Gambaran Kepatuhan Lansia dalam Mengkonsumsi Obat Antihipertensi di Wilayah Puskesmas Simpang Tiga Kota Pekanbaru - Sri Wahyuni; Didi Kurniawan; Oswati Hasanah (Universitas Bengkulu, 2023)
Elderly compliance in taking antihypertensive drugs is one of the determining factors for controlling hypertension. This study aims to determine the description of elderly compliance in consuming antihypertensive drugs in the Simpang Tiga Health Center area of ​​Pekanbaru City. This study uses a descriptive survey research method. The research sample was 96 respondents who were taken based on inclusion criteria using a purposive sampling technique. The analysis used is the univariate analysis which describes the characteristics of the respondents and the level of compliance. The result of this study shows that most of the respondents have a low level of compliance of 61.5% with the characteristics of the elderly aged 60-69 years of 86.5%. Distribution of respondents by gender, it was found that most of the respondents were women by 60.4%. Distribution of respondents based on ethnicity, it was found that most of the respondents were Malays, namely 64.6%. The highest percentage of respondents' education is SMP/equivalent at 38.5. The results of this study indicate that most of the respondents have a low level of adherence to taking medication. Research recommends that is necessary to improve the provision of health education regarding the importance of consuming antihypertensive.